PERENCANAAN PILIHAN KARIR PESERTA DIDIK KELAS VIII SEKOLAH MENENGAH PERTAMA NEGERI 6 PONTIANAK - Lion, Dominikus; Yuline, Yuline; Wicaksono, Luhur (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research  aimed to describe the steps, planning, and the role of teacher guidance and counseling in planning career choices for class VIII students in public junior high schools. The method used in this research is descriptive method with a quantitative approach. Sources of the data in this research were eighth grade students of public junior high school. The technique used in this research is technique of indirect communication and direct communication. Based on the result of data analysis it can be concluded that students know how the steps in planning career choices with an average calculation of 70,12% are in good category, students know career choice planning with an average calculation of 77,91% in the good category, dan students know well the role of counceling teachers in providing career guidance service with an average calculation of 75,00% in the good category. Keywords: Planning, Career